Leishmania in wolves in northern Spain: A spreading zoonosis evidenced by wildlife sanitary surveillance - Oleaga, Álvaro; Zanet, Stefania; Espí, Alberto; Pegoraro de Macedo, Marcia Raquel; Gortázar, Christian; Ferroglio, Ezio (Veterinary Parasitology, 2018)
Leishmaniosis is, to date, considered the second most important emerging vector-borne protozoal disease in the world after malaria. The form of zoonotic visceral leishmaniosis found in the Mediterranean basin is caused by Leishmania infantum, and its life cycle includes the domestic dog and a phlebotomine sandfly vector. This complex epidemiological cycle and its high prevalence of subclinical infection, hinder the surveillance and control of L. infantum, and allows it to go unnoticed at the geographical endemicity limits of the parasite or in recently colonized areas. We, therefore, tested 102 wolves (Canis lupus) and 47 other wild carnivores in order to detect Leishmania DNA by means of PCR. Samples were collected from 2008 to 2014 in Asturias (northern Spain), a region considered non-endemic for the parasite. The results obtained provided valuable information regarding the prevalence of Leishmania in wild carnivores in Asturias and its geographic distribution in the region: an average prevalence of 33% for wolves and an overall prevalence of 40% for all the wild carnivores studied were reported, with a widespread presence of the parasite in the region and an apparent increase in its prevalence in wolves during the last decade. This suggests the usefulness of the wolf as a sentinel species for the detection and study of Leishmania in the field and confirms the value of wildlife sanitary surveillance programs for the detection and monitoring of hitherto disregarded diseases that affect domestic animals and humans. This is a contribution to the agreement between CSIC and Principado de Asturias. Peer Reviewed